Pengembangan Bahan Ajar Terintegrasi Nilai-Nilai Islam Pada Pembelajaran Matematika - Dian Rahma Sari; Nurfadila Nurfadila; Siti Halimah; Wirdatul Akmal; Elsa Carolina; M. Imamuddin (KOLONI, 2023)
Researchers are interested in knowing more about the development of teaching materials integrated with Islamic values in learning mathematics. This study aims to thoroughly map the development of teaching materials including student worksheets, student worksheets, learning media and learning modules that integrate Islamic values and the effectiveness of the results of using these teaching materials for students. This will provide ideas for future researchers to further develop teaching materials that integrate Islamic values in mathematics learning. This study aims to enrich studies for research related to the development of teaching materials integrated with Islamic values in learning mathematics. on learning mathematics. Where researchers collect references from several national journals and these journals are journals that have been published in the Online Journal System (OJS) from 2016-2023. The researchers collected articles using Google Scholar. These findings are very complete and very extraordinary, so it is important for educators to implement this to improve the education system in Indonesia, so that it does not only focus on intellectual intelligence but also students' spiritual intelligence. In addition, by implementing Islamic-integrated learning, over time it will minimize the moral crisis that occurs in students in Indonesia. The application of integrated teaching materials with Islamic values can also increase the activity of students during the learning process so that this can lead to learning outcomes students will also increase. In addition to increasing the activeness of students in the learning process and improving student learning outcomes, it turns out that based on the results of research that these teaching materials can also increase the positive character of students because the teaching materials applied contain Islamic values. Keywords: learning mathematics integrated with Islamic values; teaching materials integrated with Islamic values